2014
DOI: 10.1177/1073191114550477
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and Adolescents’ Perspectives on Parenting

Abstract: Uncertainty persists regarding adequate measurement of parenting behavior during early adolescence. The present study aimed to clarify the conceptual structure of parenting by evaluating three different models that include support, psychological control, and various types of behavioral control (i.e., proactive, punitive, and harsh punitive control). Furthermore, we examined measurement invariance of parenting ratings by 1,111 Flemish adolescents from Grade 7 till 9, their mother, and father. Finally, criterion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 84 publications
(141 reference statements)
4
77
0
2
Order By: Relevance
“…Second, we present an applied example of the importance of testing measurement invariance across informants, particularly parents and children. Our results build on the previous work of both Dirks et al (2014) and Janssens et al (2015) by explicating that conceptual similarity across informants or shared item content on forms, are not enough. Prior to comparing mean levels of any constructs, researchers should take care to ensure that the same constructs have been captured in all groups by testing the invariance of their measurements.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Second, we present an applied example of the importance of testing measurement invariance across informants, particularly parents and children. Our results build on the previous work of both Dirks et al (2014) and Janssens et al (2015) by explicating that conceptual similarity across informants or shared item content on forms, are not enough. Prior to comparing mean levels of any constructs, researchers should take care to ensure that the same constructs have been captured in all groups by testing the invariance of their measurements.…”
Section: Discussionsupporting
confidence: 63%
“…However, we are aware of very few publications that report testing measurement invariance across parent and child reports. Janssens et al (2015) tested measurement invariance of a five-factor model of parent control behaviors underlying the Parental Behavior Scale (PBS; (Van Leeuwen et al 2013) across mothers, fathers, and their teens. The authors identified partial measurement invariance, suggesting that measurement operation was largely equivalent across informants.…”
Section: The Case For Measurement Invariancementioning
confidence: 99%
“…Consequently, in recent years research on multi-informant assessment has focused on the measurement invariance of parallel forms administered to multiple informants (e.g., Dirks et al 2014), or whether scores from reports of multiple informants can be meaningfully interpreted as carrying the same or similar psychometric properties. However, only recently have these methods begun to be applied to understanding the measurement invariance of adolescents' and parents' reports of family functioning (e.g., Gross et al 2016;Janssens et al 2015). Therefore, a second key aim of our Special Issue involves reporting research on the measurement invariance of adolescents' and parents' reports of family functioning.…”
Section: An Increased Focus On Measurement Invariancementioning
confidence: 99%
“…Items related to child behavior driven processes, such as parental monitoring or supervision practices, may be more likely to capture what children are likely to disclose to their parents about whereabouts and peer groups (Kerr & Stattin, 2000; Kerr, Stattin, & Burk, 2010). Even for well-established parenting constructs, it is likely that parents and youth are reporting information regarding the same parenting practices, but parents and youth may respond to items with different degrees of understanding during adolescence (Janssens et al, 2015). …”
mentioning
confidence: 99%